2021
DOI: 10.1097/ccm.0000000000004875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sepsis Definitions as Automated Criteria

Abstract: OBJECTIVES: Assess the impact of heterogeneity among established sepsis criteria (Sepsis-1, Sepsis-3, Centers for Disease Control and Prevention Adult Sepsis Event, and Centers for Medicare and Medicaid severe sepsis core measure 1) through the comparison of corresponding sepsis cohorts. DESIGN: Retrospective analysis of data extracted from electronic health record. SETTING: Single, tertiary-care center in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, identification of sepsis onset time is not defined in the Sepsis-3 criteria and is prone to disagreement, which can significantly alter the results. 7 , 12 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, identification of sepsis onset time is not defined in the Sepsis-3 criteria and is prone to disagreement, which can significantly alter the results. 7 , 12 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…Sepsis was defined according to the Sepsis-3 consensus statement as suspicion of infection (SOI; culture collection followed by antibiotics within 72 h or antibiotics followed by culture procurement within 24 h, Supplementary Appendix I ) accompanied by a qSOFA score ≥2. 12 Only the first sepsis event for each patient was evaluated. Time of onset was set as the time of SOI.…”
Section: Methodsmentioning
confidence: 99%
“…As we look towards the future of AI/ML in sepsis care, there are many necessary barriers that need to be overcome before wide scale deployment is achieved. These include the need for larger, more integrated datasets, a harmonized definition of sepsis suitable for automated extraction, more robust explainability, and prospective algorithm validation with emphasis on end-user needs, expectations and clinical workflows [79][80][81]. Numerous clinical studies have demonstrated that delaying the administration of antibiotic therapy, even by an hour or two in septic shock, can be associated with greater risk of death 2.…”
Section: Using Ai/ml To Improve Sepsis Outcomesmentioning
confidence: 99%
“…A recent study that used different sepsis definitions to generate patient cohorts found significant heterogeneous characteristics and clinical outcomes between cohorts. 136 Similarly, previous work by Liu et al 137 demonstrated that using different infection criteria resulted in a different number of patients and slightly different outcomes. Similar to how changes in the definition and varying coding methods can affect sepsis mortality outcomes, 138 the sepsis definition and codes used in ML studies will likely change the outcome, results, and reporting methods.…”
Section: Discussionmentioning
confidence: 85%